Metformin and Vitamin B12 Deficiency: Where Do We Stand? - Marwan Awad Ahmed (Frontiers Media S.A., 2016)
The association between metformin use and low vitamin B12 levels in type 2 diabetes mellitus patients is well-established. However, many aspects of the topic remain to be elucidated. There is still controversy on the current diagnostic approaches to vitamin B12 deficiency. It is now believed that measuring the serum levels of the vitamin may not reflect its metabolic status. Moreover, there were conflicting results from studies attempting to quantify and explore metformin-associated vitamin B12 deficiency and its clinical impacts. This article reviews the cellular functions of vitamin B12, the biomarkers utilized to define the vitamin deficiency and metformin-induced vitamin B12 deficiency with an emphasis on its prevalence and clinical impacts.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.